2014
DOI: 10.1017/s1461145714000716
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor 5 binding in patients with obsessive-compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) is a disabling, mostly chronic, psychiatric condition with significant social and economic impairments and is a major public health issue. However, numerous patients are resistant to currently available pharmacological and psychological interventions. Given that recent animal studies and magnetic resonance spectroscopy research points to glutamate dysfunction in OCD, we investigated the metabotropic glutamate receptor 5 (mGluR5) in patients with OCD and healthy controls. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 34 publications
1
32
1
Order By: Relevance
“…Dysregulation of mGluR5 in the OFC might, therefore, play a role in the association between PTSD and impulsive behaviors, including substance abuse (53), self-harm (54), and aggression (55). Interestingly, Akkus et al (56) showed a positive correlation between mGluR5 and anxiety-related symptoms in Obsessive Compulsive Disorder (OCD) using PET. There is substantial symptomatic overlap between OCD and PTSD, with fear, anxiety, and avoidance symptoms being key to both disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of mGluR5 in the OFC might, therefore, play a role in the association between PTSD and impulsive behaviors, including substance abuse (53), self-harm (54), and aggression (55). Interestingly, Akkus et al (56) showed a positive correlation between mGluR5 and anxiety-related symptoms in Obsessive Compulsive Disorder (OCD) using PET. There is substantial symptomatic overlap between OCD and PTSD, with fear, anxiety, and avoidance symptoms being key to both disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of the glutamatergic system in humans is supported by preclinical studies that suggest that striatal glutamate homeostasis is disrupted following cocaine exposure (Martinez et al, 2014), an observation made earlier in rodents (Knackstedt and Kalivas, 2009; Moussawi et al, 2009). Indeed, glutamate transmission, and particularly mGluR 1/5 , are central in mood disorders as well as the regulation of the behavioral and molecular responses to cocaine (Chiamulera et al, 2001; Swanson et al, 2001; Kalivas et al, 2005; Kenny et al, 2005; Volkow et al, 2005; Kumaresan et al, 2009; Moussawi et al, 2009; Akkus et al, 2014; Terbeck et al, 2015; Perry et al, 2016). In recent years, mGluR 5 have come in focus as promising targets for the treatment of various aspects of cocaine abuse; positive allosteric modulators of mGluR 5 facilitate extinction of cocaine-associated contextual memory (Cleva et al, 2011; Perry et al, 2016), whereas negative allosteric modulators, pharmacological blockade, or genetic deletion decrease CSA, cocaine seeking, and conditioned place preference (Chiamulera et al, 2001; Kenny et al, 2005; Kumaresan et al, 2009; Moussawi et al, 2009; Wang et al, 2013; Knackstedt et al, 2014; Gould et al, 2015; Schmidt et al, 2015; Mihov and Hasler, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The association between smoking and low mGluR5 DVR might represent a mechanism underlying the improvement of extrapyramidal side effects through nicotine consumption given that the specific pharmacological blocking of mGluR5 has emerged as one of the most attractive non-dopaminergic-based strategies in the management of motor symptoms in Parkinson's Disease (Vallano et al, 2013). Previously, we reported on a positive correlation between anxiety-related symptoms and mGluR5 DVR (Akkus et al, 2014). As a result, smoking in schizophrenia may also help to reduce some of the non-motor side effects of antipsychotics related to their effects on glutamate signaling.…”
Section: Discussionmentioning
confidence: 92%
“…Equilibrium between the tracer in tissue and blood is achieved 40 min after commencing the radio-ligand infusion (Burger et al, 2010 was administered using an infusion pump (half was given as a bolus over 2 min and the other half infused over the next 58 min). Image acquisition and reconstruction were performed as described earlier (Akkus et al, 2014;Ametamey et al, 2006;Deschwanden et al, 2011;Treyer et al, 2007), using the cerebellum as the reference region. Normalization of the images to MNI space was performed using averaged early frames image that resembles perfusion images using PMOD Fusion tool (Version 3.5).…”
Section: Positron Emission Tomographymentioning
confidence: 99%